2019
DOI: 10.1097/rlu.0000000000002818
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT in Graft Versus Host Disease–Associated Polymyositis

Abstract: Graft versus host disease (GVHD) is the most frequent and serious complication of allogenic hematopoietic stem cell transplant. Polymyositis is a rare neuromuscular manifestation of GVHD, which often responds well to corticosteroid and immunosuppression therapy. We present a case of a 38-year-old man with a known case of mixed-phenotype acute leukemia after hematopoietic stem cell transplant presenting with GVHD-associated polymyositis. 18F-FDG PET/CT done in this case not only helped in the detection of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Recently, studies on disease activity in IM using fluorodeoxyglucose‐position emission tomography/CT have revealed that FDG uptake into muscle elevates in GVHD‐related IM. This finding reflects increased local muscle metabolism, including inflammatory cell infiltration 8,9 . Nonetheless, the condition's characteristic pathology remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies on disease activity in IM using fluorodeoxyglucose‐position emission tomography/CT have revealed that FDG uptake into muscle elevates in GVHD‐related IM. This finding reflects increased local muscle metabolism, including inflammatory cell infiltration 8,9 . Nonetheless, the condition's characteristic pathology remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This finding reflects increased local muscle metabolism, including inflammatory cell infiltration. 8,9 Nonetheless, the condition's characteristic pathology remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…FDG PET-CT has already been used for different inflammatory myopathies which showed increased tracer uptake in the inflamed muscles. [ 10 11 12 13 14 15 ] Hence, it is important for nuclear medicine physicians to be familiar with FDG PET-CT findings attributable to chemotherapy induced myositis so that an appropriate differential diagnosis can be established. Our case demonstrates a rare side effect of docetaxel on 18 F FDG PET/CT.…”
mentioning
confidence: 99%